A review of Dendrophthoe pentandra (Mistletoe): phytomorphology, extraction techniques, phytochemicals, and biological activities - Awang, Mohd Azrie; Nik Mat Daud, Nik Nurul Najihah; Mohd Ismail, Nurul Izzati; Abdullah, Farah Izana; Benjamin, Mohammad Amil Zulhilmi (Multidisciplinary Digital Publishing Institute, 2023)
Dendrophtoe pentandra, popularly known as mistletoe, is a semi-parasitic plant that can grow on many host plants and is native to Southeast Asia, especially Malaysia. D. pentandra is regarded as an unfavourable plant for an economically significant horticultural plant; however, D. pentandra is also regarded as a medicinal plant and is used in traditional and alternative medicine to treat coughs, diabetes, hypertension, and cancer. Scientific research has also found that this plant has significant potential for medical properties such as antioxidant, antibacterial, anticancer, antiproliferative, antidiabetic and antihyperglycaemic, anti-inflammatory, cytotoxicity, hepatoprotective, immunomodulatory, and anti-aging properties. Numerous phytochemical compounds from D. pentandra extracts have been identified using extraction techniques such as maceration and reflux. Thus, this review aims to provide thorough information on phytomorphology, extraction techniques, phytochemicals, biological activities, and the future prospects of D. pentandra.